The Hidden Cost of Creativity: How Poster Design Competitions Facilitate Economic and Moral Rights Appropriation in Indonesia - Afriansyah Tanjung (Dialogia Iuridica, 2025)
Design competitions have become a prominent avenue for students and emerging designers in Indonesia to gain visibility, yet the copyright terms embedded in these contests often conceal significant legal and ethical risks. This study investigates whether poster design competitions genuinely empower creators or instead function as mechanisms for the systematic appropriation of economic and moral rights. Using an empirical legal research methodology with qualitative online ethnography, the study observes competition cycles across ministries, local governments, universities, and private institutions. Competition guidelines, terms and conditions, and post-competition publications were coded to identify patterns of copyright transfer, exclusivity obligations, and moral rights waivers, these findings were interpreted against Indonesia’s 2014 Copyright Law and broader socio-legal scholarship. The analysis reveals that many competitions require participants to automatically transfer full copyright ownership merely by submitting their work without a valid written agreement rendering such transfers legally defective. Moreover, several competitions implicitly or explicitly demand waivers of moral rights, which are inalienable under Indonesian law. These practices compromise fair attribution, limit portfolio development, and disadvantage young designers who rely on credited works for career advancement. Rather than fostering creativity, many competitions replicate power imbalances and extract value from creators without adequate recognition or compensation. By exposing how design competitions blur the line between opportunity and exploitation, this study invites deeper reflection on the governance of creative labor in Indonesia. The findings underscore the need for clearer contractual safeguards and regulatory oversight to ensure that competitions operate ethically, legally, and in genuine support of creative development.